Mídias digitais interativas: perspectivas de níveis, graus e modelos - Amaral, Reginaldo Gonçalves do (2009)
This dissertation explores, from the media convergence, the interactive digital media, and its several manifestations (great social coverage, possibility of access, and democratization of information). The topic, which emerges from digital technologies, deals with the present essence of discussions. The research involves a reflection about the possibilities that the media convergence can provide to the interactivity, also about the present situation, as well as the development trends of the interactive levels, degrees, and models, in a medium term. It was taken into account the advent of the digital television, and the discussions about the interactivity in the electronic and digital media. Some questions were focused concerning to interactivity: if it can change a communication media from one-all to all-all ; if it can change a great potential media like the TV into a multimedia as it is in fact the Internet; or if it can generate a democratization of information as the political speech proposes. It became clear that the main difficulty to establishes a comparative analysis among the interactive media resides in the lack of DTV throughout the country. The approach was based on theoretical bibliography of contemporary authors (academic or not), like: Lev Manovich, Ken Freed, Pierre Lévy, Arlindo Machado, and Lúcia Santaella, as well as followed studies carried out in Brazil. The work had as purpose to contribute for the understanding of interactivity in the present social context, and of the perspectives formed within the media convergence